Pesantren Kilat Ramadan as a The Depths of The Religious Sciences and Akhlak Plantation at The al-Wafa Antapani Bandung Mosque - Ihsan, Nur Hadi; Putri, Humaira Agam; Sansayto, Ide Mafaza (Yayasan Rahmat Islamiyah, 2023)
Ramadan is the right time to add insight and religious knowledge of children. Pesantren kilat is an alternative means to add knowledge and religious experience. Pesantren kilat Program is designed very varied so that children do not get bored to follow it. Some religious materials are taught to them in a short but varied and fun time. The main purpose of this activity is for children to learn more about religion and instill good morals in them. This Program is carried out by the PAR (Participatory Action Research) method, which is a research process through empowerment and social change by involving respondents actively and directly, then facilitated to jointly improve and improve the quality of life. The result of this program is that children are expected to continue to explore the science of religion and practice it in everyday life.